Kebijakan Perencanaan Tata Guna Tanah Berbasis Lingkungan Hidup - Arba - (Fakultas Hukum Universitas Mataram, 2011)
Land is the most strategic natural resources and has an essential role in human life, therefore the preparation, allotment, and utilization of the land should to be planed well and aright in other to have the most benefit for the prosperity of the most society. The planning, preparation, allotment, and utilization the land is conducted to regulate of mastery and ownership and utilization of land by person, corporation or a group of society, so that it is regulated and not prejudiced each other. The regulation of land by government base on some instruments of law consist of: Article 33 section (30) UUD 1945, UUPA (Agrarian Acts) Article 6, 14, and UUTR (Space Regulation Acts) Number 24 Year 1992 that to be changed with UUTR Number 26 Year 2007; UULH (Environmental Acts) Number 4 Year 1982 that to be changed with UUPLH (Environmental Management Acts) Number 23 Year 1997, and to be changed anymore with UUPPLH (Environmental Management and Protection Acts) Number 32 Year 2009; and PP (Governmental Regulation) Number 16 Year 2004 about the Land Use Planning. The management of lands use planning base on the cohesiveness principle, empower and efficiency principle, harmonization and equal principle, sustainable principle, transparency principle, and equality, fairness and protection of law principle. The relevance between land use planning and environment is that, the planning, preparation, allotment, and utilization of land really have to pay attention many aspects, either the aspect of personal or society interest, aspect of maintenance and preservation of natural resources itself, or aspect of protection and preservation of Environment.